The Effects of a Complex Shoulder Exercise Program with Respiratory Training on Muscle Activity and Posture in Individuals Exhibiting Scapular Internal Rotation - Xin Yan; Xing-Han Zhou; Tae-Ho Kim (Applied Sciences)
The purpose of this study was to compare the effects of a complex shoulder exercise program including respiratory training with those of a similar program including thorax-stabilization exercises on muscle activity and posture in individuals exhibiting scapular internal rotation. The subjects of this study were 32 adults with scapular internal rotation. The exercise group performed the complex shoulder exercise program with respiratory training (EG), while the control group performed the complex shoulder exercise program with thorax-stabilization exercises (CG). After 4 weeks of training, the changes in muscle activity and posture were measured. The differences between the two groups were assessed through comparative analysis using an independent t-test. The paired t-test revealed significant disparities in craniovertebral angle (CVA) and sagittal shoulder angle (SSA) posture between the measurements before and after the programs (p < 0.05). Additionally, the paired t-test indicated notable differences in muscle activity of the upper trapezius (UT), middle trapezius (MT), lower trapezius (LT), and serratus anterior (SA) muscles (p < 0.05). According to the findings, both intervention groups presented significant improvements in cervical and shoulder posture and muscle activity. Consequently, combination of the complex shoulder exercise program with either respiratory training or thorax-stabilization exercises had a favorable impact on posture and muscle activity among individuals exhibiting scapular internal rotation.